Changes in the Sulphur Content of Winter Wheat in a Field Experiment - Mars, Éva (Acta Agraria Debreceniensis, 2004)
The use of superphosphate as P-containing fertiliser decreased in the last years in many countries in accordance with strict air pollution laws, and the S-deposition decreased from the atmosphere to the soil as well.Winter wheat is the one of the S-demanding plants. Recently, the gradually increasing S absence endanger the formation of required average yield of winter wheat, and has bad effect on its quality.We examined the effect of treatments on the sulphur-, nitrogen content and the N/S ratio of winter wheat in the whole upperground plant and in the grain and straw at harvest in a arable land sulphur fertilization experiment on brown forest soil (Agricultural Company of Felsőzsolca).We analysed the samples from spring to harvesting, in the critical phenophases. In this study we discuss only the values from the stooling and stalking and the results of analysis of grain and straw in the harvest.We experienced that the concentration of sulphur in the whole upperground parts of winter wheat showed increase to the end of vegetation independently of fertilization. The N/S ratio was between 8% and 12% in the beginning of the growth period in the whole upperground plant, while the ratio in the grain at harvest was between 13 and 14%. When we examined the whole upperground plant, stalk and leaf at stalking, we got the highest sulphur content in the leaf. Mostly the middle level sulphur fertilization dose (4 l/ha) increased the sulphur accumulation in the green plant. At total maturing, the greatest part of accumulated sulphur is in the grain, but then the effect of fertilization is less glaring.